Modification and testing of KAU Arecanut De-husker - Rajmohan C K (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 1996)
An arecanut dehusker consisting of mainly a pair of fluted rollers, a pressure roller assembly, a scrapper assembly, a guide chute and a feed tray was developed in this study. The arecanut was fed between the two counter- rotating fluted rollers and was pressed against these rollers by the pressure roller. The fluted rollers gripped the husk and pulled it to the rear side of the rollers. In the process the husk was ripped open and the kernel was ejected from its shell.